Antigen-independent, autonomous B cell receptor signaling drives activated B cell DLBCL - Eken, Janneke A.; Koning, Marvyn T.; Kupcova, Kristyna; Sepulveda Yañez, Julieta Haydee; de Groen, Ruben A. L.; Quinten, Edwin; Janssen, Jurriaan; van Bergen, Cornelis A. M.; Vermaat, Joost S. P.; Cleven, Arjen; Navarrete Signorile, Marcelo Alejandro; Ylstra, Bauke; et al. (My University, 2024)
This study describes and characterizes antigen-independent, autonomous signaling of the clonal B cell receptor as an intrinsic oncogenic driver in activated B cell type DLBCL. This long-sought non-genetic lymphomagenic mechanism has profound implications for development of effective novel therapies. Diffuse large B cell lymphoma of activated B cell type (ABC-DLBCL), a major cell-of-origin DLBCL subtype, is characterized by chronic active B cell receptor (BCR) signaling and NF-kappa B activation, which can be explained by activating mutations of the BCR signaling cascade in a minority of cases. We demonstrate that autonomous BCR signaling, akin to its essential pathogenetic role in chronic lymphocytic leukemia (CLL), can explain chronic active BCR signaling in ABC-DLBCL. 13 of 18 tested DLBCL-derived BCR, including 12 cases selected for expression of IgM, induced spontaneous calcium flux and increased phosphorylation of the BCR signaling cascade in murine triple knockout pre-B cells without antigenic stimulation or external BCR crosslinking. Autonomous BCR signaling was associated with IgM isotype, dependent on somatic BCR mutations and individual HCDR3 sequences, and largely restricted to non-GCB DLBCL. Autonomous BCR signaling represents a novel immunological oncogenic driver mechanism in DLBCL originating from individual BCR sequences and adds a new dimension to currently proposed genetics- and transcriptomics-based DLBCL classifications.
Keywords: breakpoint cluster region